Neural Network Solution to the Cogeneration System by Using Coal - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2008)
Thermodynamic analysis of power plants that generate electricity with the use of coal requires quite a complex and sophisticated mathematical model. In this study relationships between electricity produced in power plant and properties of coal used in cogeneration systems was investigated by using Artificial Neural Network (ANN) with backpropagation learning method. In this method two types of ANN models; single and multi-layer model were used and training with the multi-layer model gave us better result (R-2=0,954) than the single layer model which is quite represent the system.
Keywords: Artificial Neural Networks; Coal; Electricity; Backpropagation Algorithm